Developing Instructional Media Android-Based for Building Computational Thinking Skills for High School Students : Pengembangan Media Pembelajaran Berbasis Android untuk Membangun Keterampilan Berpikir Komputasional Siswa SMA - Murniatiningtyas, Diana; Degeng, I Nyoman Sudana; Sitompul, Nurmida Catherine (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to develop android-based instructional media to build computational thinking skill for High School students using the ADDIE Model. Computational thinking is studied in informatics subjects. The development product has gained an expert feasibility assessment and tested on students. The research instruments are questionnaires and test. Experts include content experts, instructional media experts, and instructional design experts. Trials to students consist of one-on-one evaluation, small group evaluation and tryout or classroom. The results of the assessment of experts show that the product is very feasible to use as instructional media. Small group evaluation and tryout at classroom shown that the product is categorized as very feasible to be used as multimedia to develop computational thinking. The effectiveness of product development is measured by pretest and posttest. The effectiveness test results show a t-test value of -14.162 with a significance level of 0.000 (p value < 0.05), meaning that there is a difference in the average value of the pretest and posttest. Thus, the use of C-Think as an instructional media is effectively to improve computational thinking skills of high school students. Highlights: Development Process: Utilizing the ADDIE Model ensures systematic development of instructional media for effective learning outcomes. Expert Evaluation: Expert feasibility assessment validates the quality and appropriateness of the developed instructional media. Effectiveness Testing: Pretest-posttest analysis demonstrates significant improvement in computational thinking skills among high school students using the developed Android-based instructional media. Keywords: Computational Thinking, Informatic Subject, Media Android-Based